UNVEILING THE EXPANDING CLINICAL HORIZONS OF BOTULINUM TOXIN ACROSS MEDICAL SPECIALITIES - Katarzyna Herjan; Piotr Armański; Gabriela Łocik; Marta Bonarska; Joanna Wróbel; Katarzyna Kozon (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Originally identified for its potent neurotoxicity, botulinum toxin (BoNT) has been successfully repurposed into a highly versatile agent used across numerous medical specialities. Through targeted inhibition of acetylcholine release at neuromuscular synapses, BoNT induces localized, reversible muscle relaxation, effectively alleviating symptoms in a variety of neuromuscular and autonomic disorders.Aim: This review aims to highlight the approved therapeutic uses of BoNT, its expanding applications, and the importance of proper technique and anatomical knowledge in maximizing efficacy and minimizing adverse events.Materials and Methods: A comprehensive literature review was conducted to evaluate current therapeutic indications, mechanisms of action, safety profile, and emerging uses of BoNT.Results: Approved therapeutic indications include dystonias, spasticity, chronic migraine, hyperhidrosis, bruxism, while growing evidence supports its emerging role in pain management, selected psychiatric disorders and certain cardiovascular conditions. In aesthetic medicine, BoNT remains primary non-surgical option for addressing dynamic facial lines and hyperfunctional musculature. The safty profile of BoNT remains favorable, however, the efficacy and safety of BoNT is strongly linked to appropriate dosing, product selection, formulation and precise injection technique, emphasizing the critical role of anatomical knowledge to maximize therapeutic benefit while minimizing adverse events.Conclusion: Botulinum toxin has evolved from a potent neurotoxin to a valuable therapeutic agent across a broad range of medical disciplines. Its continued success depends on deep understanding of anatomy, product characteristics, and injection technique. Ongoing research into novel serotypes, delivery systems, and expanded indications will further solidify BoNT’s role as a cornerstone in both therapeutic and aesthetic practice.